Potential of whole-genome sequencing for determining risk and personalizing therapy: focus on AML. Issue 10 (October 2012) - Borate, Uma; Absher, Devin; Erba, Harry P; Pasche, Boris
In spite of recent advances in molecular diagnostic techniques and expanded indications for allogeneic hematopoietic stem cell transplantation, treatment of acute myeloid leukemia (AML) remains a major challenge. In the last decade, several recurrent genetic abnormalities and gene mutations with prognostic implications have been identified. This has led to improved informed treatment decisions. However, there has been limited change in the use of nonspecific cytotoxic chemotherapy and mortality rates continue to be unacceptably high, with 5 year overall survival rates of older AML patients at 30% or less. Whole-genome sequencing offers hope for greater diagnostic accuracy and is likely to lead to further characterization of disease subsets with differential outcome and response to treatment. The holy grail of personalized targeted therapy for the individual AML patient, while minimizing toxicity and prolonging survival, appears closer than ever.